Assessment the Suicidal Ideation Among Secondary School Students: Menilai Ide Bunuh Diri di Kalangan Siswa Sekolah Menengah - Aqeel Shrshabar; Ayad Majid Mousa (Academia Open, 2025)
Background: Suicidal ideation among adolescents is a critical public health issue, influenced by various psychosocial factors such as bullying. Specific Background: The prevalence of bullying and its relationship to suicidal ideation remains underexplored in the context of secondary school students in Dhi Qar Governorate, Iraq. Knowledge Gap: While existing studies have addressed bullying and suicide, the specific impact in this region and its demographic characteristics remain unclear. Aims: This study aimed to evaluate the prevalence of suicidal ideation among secondary school students and its correlation with bullying experiences. Methods: An observational cross-sectional descriptive study was conducted using a demographic questionnaire and the Suicidal Ideation Questionnaire, with 380 secondary school students from Dhi Qar Governorate. Results: The findings indicated a low prevalence of bullying but a significant correlation between bullying and suicidal ideation. Although most participants did not experience suicidal thoughts, those subjected to bullying were more likely to report such thoughts. Novelty: This study provides new insights into the psychological health of secondary school students in Iraq, particularly regarding bullying and suicidal ideation. Implications: The results highlight the need for psychological support programs in schools to mitigate bullying’s impact on mental health, with further research recommended to expand the sample size and regional scope. HIghlights: Correlation: Bullying linked to increased suicidal ideation among secondary school students. Prevalence: Over 50% experienced some degree of bullying. Recommendations: Psychological support programs needed in schools. Keywords: Suicidal ideation, bullying, secondary school, Iraq, psychological support